2012
DOI: 10.1371/journal.pone.0046240
|View full text |Cite
|
Sign up to set email alerts
|

When Less Is More: Evolutionary Origins of the Affect Heuristic

Abstract: The human mind is built for approximations. When considering the value of a large aggregate of different items, for example, we typically do not summate the many individual values. Instead, we appear to form an immediate impression of the likeability of the option based on the average quality of the full collection, which is easier to evaluate and remember. While useful in many situations, this affect heuristic can lead to apparently irrational decision-making. For example, studies have shown that people are w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 80 publications
(110 reference statements)
4
51
0
1
Order By: Relevance
“…We subsequently conducted an affective decision-making study with these monkeys as well as with free-ranging rhesus monkeys at the Caribbean Primate Research Center on Cayo Santiago in Puerto Rico [45]. We obtained the same general findings in the laboratory and field, suggesting that the laboratory conditions are not significantly biasing experimental results, and that the subjects in the current study are representative of rhesus monkeys in general [46].…”
Section: Methodsmentioning
confidence: 66%
“…We subsequently conducted an affective decision-making study with these monkeys as well as with free-ranging rhesus monkeys at the Caribbean Primate Research Center on Cayo Santiago in Puerto Rico [45]. We obtained the same general findings in the laboratory and field, suggesting that the laboratory conditions are not significantly biasing experimental results, and that the subjects in the current study are representative of rhesus monkeys in general [46].…”
Section: Methodsmentioning
confidence: 66%
“…For instance, monkeys willingly ate a piece of sliced vegetable or a grape but when offered a choice between them, showed a clear preference for the grape over the vegetable slice. However, surprisingly, when they were offered a choice between a single grape and a grape plus a slice of vegetable, they reliably preferred the single grape (Kralik et al, 2012).…”
Section: The Less Is More Effectmentioning
confidence: 94%
“…Much like the evolutionary origins of moral values, intuitive and analytic thinking evolved in our early ancestors (Bekoff, 2001;Evans, 2006;Evans & Stanovich, 2013). Intuitive thinking is evolutionary ancient (Evans, 2010) as such we share this capacity for thinking in this way with other species (Brosnan et al, 2007;Kralik, Xu, Knight, Khan, & Levine, 2012). Non-human primates such as chimpanzees (Pan troglodytes) (Brosnan et al, 2007;Eckert, Call, Hermes, Herrmann, & Rakoczy, 2018) and rhesus macaque (Macaca mulatta) (Hayden, Heilbronner, Nair, & Platt, 2008;Kralik et al, 2012) have been observed to rely on intuitive thinking.…”
Section: Cognitive Ability and Cognitive Style: Intuitive And Analytimentioning
confidence: 99%
“…Intuitive thinking is evolutionary ancient (Evans, 2010) as such we share this capacity for thinking in this way with other species (Brosnan et al, 2007;Kralik, Xu, Knight, Khan, & Levine, 2012). Non-human primates such as chimpanzees (Pan troglodytes) (Brosnan et al, 2007;Eckert, Call, Hermes, Herrmann, & Rakoczy, 2018) and rhesus macaque (Macaca mulatta) (Hayden, Heilbronner, Nair, & Platt, 2008;Kralik et al, 2012) have been observed to rely on intuitive thinking. Moreover, non-primate species, of which we share a common ancestor, have demonstrated a capacity for intuitive thinking too, for example, pigeons (Fantino, Kanevsky, & Charlton, 2005).…”
Section: Cognitive Ability and Cognitive Style: Intuitive And Analytimentioning
confidence: 99%